The business of changing the world how billionaires, tech disrupters, and social entrepreneurs are transforming the global aid industry - Kumar, Raj. (Boston Beacon Press, 2019)
Today, entrepreneurs, Silicon Valley start-ups, and celebrity activists are the driving force in a radical shift in the way we think about lifting people out of poverty. In this new era of data-driven, results-oriented global aid it's no longer enough to be a well-intentioned do-gooder or for the wealthy to donate an infinitesimal part of their assets to people without a home or basic nutrition. What matter now in the world of aid are measurable improvements and demonstrable, long-term change.
Includes Index
Keywords: Philanthropists; Humanitarianism; Economic assistance; International relief; Social entrepreneurship